A Study of Environmental Knowledge and Attitudes of Secondary Students in terms of Different Kinds of Schools - Elif SÖNMEZ; Zekeriya YERLİKAYA (Alınteri sosyal bilimler dergisi, 2017)
As environmental problems prominently appear day by day, the root of the problem features different perspectives and specifically environmental education. Therefore, the researches concerning the roots of the problem must be renewed. In this regard, the purpose of the present study is to compare environmental knowledge and environmental attitudes of students who study at 8th grade in different kinds of schools. In the study which is in scanning method, was carried out with 604 8th grade students who enroll in eleven different secondary schools including one private school(19 students) and one religious vocational school(32 students) in the city of Kastamonu. In the study, “Environmental Knowledge Test “and “Environmental Attitude Scale “, which were parepared for primary education school students, were used. To classify the data frequencies and to compare the differences between the groups except the averages Anova test was used. As a result of the study, it has been observed that there are significant differences in private school, religious vocational school and classic secondary school students in terms of environmental knowledge. In terms of environmental attitudes, while there are differences in private secondary school and religious vocational school students, there are no differences in classic secondary school students.